SHP099-containing multi-targeting hydrogel promotes rapid skin reconstruction through modulating a variety of cells - Liu, Zhixiao; Chen, Lei; Hao, Bingbing; Hou, Yijin; Lv, Chuan; Zhu, Yuanjie; Han, Chaofeng (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAdult wound scarring result in functional skin deficits. However, the development of effective measures to modulate the entire wound healing to encourage the skin function reconstruction is still a clinical challenge, as multiple cells are involved in wound healing hierarchically. Hydrogel scaffolds with long-lasting local release provide new insights into the clinical relevance of entire wound healing.MethodsHerein, a multi-targeting hydrogel loaded with SHP099 (Gel-SHP) is designed to modulate multiple cells during wound repair.ResultsOur results show that Gel-SHP promotes rapid reconstruction of wound skin by modulating macrophages in the inflammatory stage, fibroblasts in the regeneration stage and smooth muscle cells in the remodelling stage. Gel-SHP could increase M2 macrophage differentiation and remodel the dermal shell of hair follicles through in situ release. Moreover, Gel-SHP may modulate myofibroblasts to promote wound contraction through SHP099-scaffold synergistic interactions.DiscussionOur results provide new insights into the design of functional hydrogels for tissue regeneration applications. Gel-SHP as a promising tool could provide new clues and new research paradigms for future studies and understanding of the wound healing process and dermal shell formation.